Using self‐report to explore the relationship between anxiety and quality of life in children on the autism spectrum. Issue 10 (17th June 2019) - Adams, Dawn; Clark, Megan; Keen, Deb
Abstract : Anxiety is now recognized as one of the most common conditions that co‐occur with autism. While there has been increased research describing the typical and autism‐specific anxiety symptomatology and assessing the effectiveness of potential interventions, there has been less research exploring the impact that elevated anxiety may have on an individual and their quality of life (QoL). This study aimed to explore the impact of anxiety on the QoL in children on the autism spectrum. Children and young adolescents on the spectrum were invited to participate in a self‐report study measuring anxiety and health‐related QoL (HRQoL). The sample consisted of 71 children, aged 6–13. Children who scored above the cut off for elevated anxiety on the autism‐specific measure of anxiety (ASC‐ASD) had poorer total HRQoL and poorer scores on the social, emotional, physical, and school functioning QoL domains. Regression analyses indicate that children's self‐reported ratings of difficulties with uncertainty on the ASC‐ASD predicted all domains of HRQoL, with higher levels of difficulty with uncertainty predicting poorer HRQoL. Elevated levels of anxious arousal were also predictive of poorer physical functioning. This study highlights the importance of exploring the impact of anxiety on individuals on the spectrum and suggests that using carefully planned interventions to reduce difficulties with uncertainty may be a potential way to work toward improving the QoL of children on the spectrum. Autism Res 2019, 12: 1505–1515 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Research has shown us that individuals on the autism spectrum are more likely to have poor "quality of life" or general well‐being. Because many individuals with a diagnosis on the autism spectrum also receive a diagnosis of anxiety, this study looked at whether a child's autism symptoms or their anxiety have a bigger impact on their quality of life. Children on the autism spectrum completed questionnaires and the results showed us that one factor, difficulty with uncertainty, had the biggest impact on the child's quality of life.